DNA barcode identification of shark fillet reveals fraudulent commerce in Brazil. Issue 2 (3rd April 2019) - Calegari, Bárbara B.; Reis, Roberto E.; Alho, Clarice S.
Abstract: Fraudulent mislabeling of fish products has been reported with some frequency, representing an important problem in the food industry and regulatory agencies of many countries. This case reports a fraudulent substitution of shark fillets for the much cheaper Striped-catfish, in a large purchase for public elementary school meals in a Brazilian town. The economic and nutritional aspects involving such mislabeling demonstrate a serious fraud that should alarm governmental regulatory agencies to implement a more rigorous and frequent monitoring system on the species verification to guarantee the safety and quality of seafood.